2023
DOI: 10.3389/fgene.2022.1089375
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of the ZF-HD gene family in pea (Pisum sativum L.)

Abstract: Pea is a conventional grain-feed-grass crop in Tibet and the only high-protein legume in the region; therefore, it plays an important role in Tibetan food and grass security. Zinc finger-homeodomain (ZF-HD) belongs to a family of homozygous heterotypic cassette genes, which play an important role in plant growth, development, and response to adversity stress. Using a bioinformatics approach, 18 PsZF-HD family members were identified. These genes were distributed across seven chromosomes and two scaffold fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In embryonic seed, we found an overrepresentation of GRF, HD‐ZIP and ZF‐HD families regulated by WD. The ZF‐HD family has recently been identified in the pea genome and its role in drought resistance has been reported in multiple plant species (Shi et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…In embryonic seed, we found an overrepresentation of GRF, HD‐ZIP and ZF‐HD families regulated by WD. The ZF‐HD family has recently been identified in the pea genome and its role in drought resistance has been reported in multiple plant species (Shi et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Elements related to stress responses were found in PeZF-HD promoters, including MYB, MBS, LTR, TCA-element, TC-rich repeats and ABRE (Table S1), which are directly related to ABA, drought, cold and salt stress responses. ZF-HD genes were reported to be involved in various abiotic stresses and ABA treatment, such as salt and drought stress [12,17,19,34]. Moreover, ZF-HD genes in alfalfa also showed similarly decreased expression levels under alkaline stress [31].…”
Section: Discussionmentioning
confidence: 99%
“…As a transcriptional regulator, zinc finger-homeodomain (ZF-HD) has received increasing attention due to its pivotal roles in modulating plant growth, development, and responses to various biotic and abiotic stresses. Research has shown that ZF-HD transcription factors have been identified in various plants such as A. thaliana (14) [13], Malus domestica (19) [32], Pisum sativum (18) [33], Gossypium hirsutum (49), Gossypium barbadense (50), Gossypium arboretum (22), and Gossypium raimondii (32) [34]. Although ZF-HDs have been discovered in numerous plants, there remains a paucity of research regarding their specific functions within orchids.…”
Section: Discussionmentioning
confidence: 99%